Pelatihan Pembuatan Instrumen Tes Diagnostik Fisika untuk Mengetahui Miskonsepsi pada Peserta Didik - Permana, Handjoko; Bakri, Fauzi (MJI Publisher by PT Mitra Jurnal Indonesia, 2022)
Abstract Many physics subjects become a scourge for most students because of the many formulas and concepts that must be understood. Teachers need help to assess the learning outcomes of their students. The use of objective tests in the form of multiple-choice tests, which are widely used today, has many areas for improvement. The